Nitrogen Utilization and Metabolism in Ruminococcus albus 8 - Kim, Jong Nam (American Society for Microbiology, 2014)
The model rumen Firmicutes organism Ruminococcus albus 8 was grown using ammonia, urea, or peptides as the sole nitrogen source; growth was not observed with amino acids as the sole nitrogen source. Growth of R. albus 8 on ammonia and urea showed the same growth rate (0.08 h(−1)) and similar maximum cell densities (for ammonia, the optical density at 600 nm [OD(600)] was 1.01; and for urea, the OD(600) was 0.99); however, growth on peptides resulted in a nearly identical growth rate (0.09 h(−1)) and a lower maximum cell density (OD(600) = 0.58). To identify differences in gene expression and enzyme activities, the transcript abundances of 10 different genes involved in nitrogen metabolism and specific enzyme activities were analyzed by harvesting mRNA and crude protein from cells at the mid- and late exponential phases of growth on the different N sources. Transcript abundances and enzyme activities varied according to nitrogen source, ammonia concentration, and growth phase. Growth of R. albus 8 on ammonia and urea was similar, with the only observed difference being an increase in urease transcript abundance and enzyme activity in urea-grown cultures. Growth of R. albus 8 on peptides showed a different nitrogen metabolism pattern, with higher gene transcript abundance levels of gdhA, glnA, gltB, amtB, glnK, and ureC, as well as higher activities of glutamate dehydrogenase and urease. These results demonstrate that ammonia, urea, and peptides can all serve as nitrogen sources for R. albus and that nitrogen metabolism genes and enzyme activities of R. albus 8 are regulated by nitrogen source and the level of ammonia in the growth medium.